Grounding Line Remote Operated Vehicle (GROV) Survey of the Ice Shelf Cavity of Petermann Glacier, Greenland - E. Rignot; N. Chauche; R. Gadi; Shivani Ehrenfeucht; Enrico Ciraci (Geophysical Research Letters)
Abstract The melting of glaciers by ocean waters along the ice sheet periphery is a major physical process driving glacier evolution in a changing climate. Using a fiber‐optic‐tethered Grounding line Remote Operated Vehicle, we explore the ice shelf cavity of Petermann Glacier, in Northwestern Greenland, with an interferometric multibeam sonar operating with 360° viewing capability. We detect a uniform seafloor at 820 m depth, 200 m deeper than anticipated. The ice shelf base reflects spatial variations in ice melt with no apparent signature at the surface, including widespread ice terraces interrupted by 30–40 m ice cliffs connected to a smooth, central basal channel that deviates by many 10 m's from flotation and experiences differential melt along its sides. Water stratification at the base of the center channel is prone to diffusive convection instead of a fully‐developed turbulent state. The results illustrate the critical importance of exploring cavities in situ.